Gender differences in preference for reward frequency versus reward magnitude in decision-making under uncertainty. (1st December 2018) - Cornwall, Astin C.; Byrne, Kaileigh A.; Worthy, Darrell A.
Abstract: Extensive research has focused on gender differences in intertemporal choices made from description in which participants must choose from multiple options that are specified without ambiguity. However, there has been limited work examining gender differences in intertemporal choices made from experience in which the possible payoffs among choice alternatives are not initially known and can only be gained from experience. Other work suggests that females attend more to reward frequency, whereas males attend more to reward magnitude . However, the tasks used in this research have been complex and did not examine intertemporal decision-making. To specifically test whether females are more sensitive to reward frequency and males are more sensitive to reward magnitude on intertemporal decisions made from experience, we designed a simple choice task in which participants pressed a response button at a time of their own choosing on each of many trials. Faster responses led to smaller, but more frequent rewards, whereas slower responses led to larger, but less frequently given rewards. As predicted, females tended to respond quicker for more certain, smaller rewards than males, supporting our prediction that women attend more to reward frequency whereas men attend more to reward magnitude. Highlights: Participants performed an experience-based probabilistic intertemporal choice task. Responding sooner led to consistent, small rewards. Responding later led to larger rewards, but greater risk of gaining nothing. Males preferred to wait longer for the possibility of larger rewards. Females preferred to respond sooner and consistently gain smaller rewards.